How Effective Are the Post-9/11 U.S. Counterterrorism Policies Within and Outside the United States? - Güler, Ahmet (Criminal justice policy review, 2024)
This study examined the effectiveness of post-9/11 U.S. counterterrorism policies in preventing terror attacks and reducing casualties against American targets within and outside the United States. Monthly data on terrorism incidents from July 1981 through December 2020 were obtained from the Global Terrorism Database (N = 462). The results of monthly interrupted time-series analyses showed that within the United States, after the 9/11 attacks, the number of attacks, the number of successful attacks, and the successful attack rate statistically significantly decreased in the first month following 9/11; then, no significant increase was observed in the trend of those outcomes. Outside the United States, after the 9/11 attacks, the trend of the number of successful attacks, the number of victims, the number of nonfatal victims, and the victim rate statistically significantly decreased. The results suggest that post-9/11 U.S. counterterrorism policies are effective both domestically and internationally. These findings and their policy implications are discussed.